Adulteration and Substitution in Indian Medicinal Plants: A Review Article - Rathore, Bhawani Singh; Kotecha, Mita; Chaudhary, Krutika; Manjula (International Research Journal of Ayurveda & Yoga, 2022)
Introduction: Ayurveda is a system of traditional alternative medicine in India. In 20th and 21st century, due to side effects of synthetic drugs, there is an increasing interest in Ayurveda proprietary medicines. At present, the adulteration and Substitution of the herbal drugs is the burning problem in herbal industry. The deforestation and extinction of many species and incorrect identification of many plants has resulted in adulteration and substitution of raw drugs. The future depended upon reliable methodologies for correct identification, standardization and quality assurance of Ayurvedic drugs. This article throws light on the concepts of substitution given by our preceptors and analyzes these with the present-day prevailing trend of adulteration and substitution, thereby aiming at systematic strategy to correctly identify the drugs. Method: Classical and modern literature along with various Research articles were gone through to collect minute details. Result: There are different types of Adulterants viz. substandard, inferior, artificial or exhausted drugs. There are many reasons of Adulteration viz. confusion in Vernacular Names, lack of knowledge about authenticsource, similarity in morphology, lack of authentic plant, similarity in color, careless collections, etc. There are various types of Substitution viz. using totally different drug, substitution of the species belonging to same family, using different parts of the plant, due to same in action. Analysis and Discussion: With the help of this thorough review, it is clear that with few basic identification points, one can easily differentiate between adulterated and original drug. Hence, the dealers and handlers of drugs should be made aware of these through training programmes.